Comprehensive Effects of Flowering Locus T-Mediated Stem Growth in Tobacco - Wu, Jun; Wu, Qiuhong; Bo, Zhongjian; Zhu, Xuli; Zhang, Junhui; Li, Qingying; Kong, Wenqing (Frontiers in Plant Science, 2022)
In flowering plants, Flowering locus T (FT) encodes a major florigen. It is a key flowering hormone in controlling flowering time and has a wide range of effects on plant development. Although the mechanism by which FT promotes flowering is currently clearly understood, comprehensive effects of the FT gene on plant growth have not been evaluated. Therefore, the effects of FT on vegetative growth need to be explored for a complete understanding of the molecular functions of the FT gene. In this study, the Jatropha curcas L. FT gene was overexpressed in tobacco (JcFTOE) in order to discover multiple aspects and related mechanisms of how the FT gene affects plant development. In JcFTOE plants, root, stem, and leaf development was strongly affected. Stem tissues were selected for further transcriptome analysis. In JcFTOE plants, stem growth was affected because of changes in the nucleus, cytoplasm, and cell wall. In the nucleus of JcFTOE plants, the primary effect was to weaken all aspects of DNA replication, which ultimately affected the cell cycle and cell division. The number of stem cells decreased significantly in JcFTOE plants, which decreased the thickness and height of tobacco stems. In the cell wall of JcFTOE plants, hemicellulose and cellulose contents increased, with the increase in hemicellulose associated with up-regulation of xylan synthase-related genes expression. In the cytoplasm of JcFTOE plants, the primary effects were on biogenesis of ribonucleoprotein complexes, photosynthesis, carbohydrate biosynthesis, and the cytoskeleton. In addition, in the cytoplasm of JcFTOE plants, there were changes in certain factors of the core oscillator, expression of many light-harvesting chlorophyll a/b binding proteins was down-regulated, and expression of fructose-1,6-bisphosphatase genes was up-regulated to increase starch content in tobacco stems. Changes in the xylem and phloem of JcFTOE plants were also identified, and in particular, xylem development was affected by significant increases in expression of irregular xylem genes.